Comparative diagnosis of the alveolar antral artery canal in the lateral maxillary sinus wall in corresponding panoramic radiography and cone-beam computed tomography - Ali-Reza Ketabi; Stefan Hassfeld; Hans-Christoph Lauer; Andree Piwowarczyk (SpringerOpen, 2023)
Abstract Purpose Sinus lift operations are a tried and tested means of providing adequate implant prosthetics to patients with compromised jawbones. Knowledge of the arterial supply of the maxillary sinus region is essential for surgical treatment in this area. The aim of the present comparative study was to determine whether alveolar antral artery (AAA) canal can be diagnosed both in corresponding panoramic radiography (PR) and cone-beam computed tomography (CBCT). Methods A total of 335 patients with 635 sites and corresponding maxillary sinus in both PR and CBCT were selected and examined for AAA canal visibility. Results The visibility of the AAA canal was significantly higher in CBCT than in PR. A total of 154 (46.0%) AAA canals could be identified in the maxillary sinus on the right. However, only four (1.2%) of these were also visible in PR. The detected values of the AAA canals in the maxillary sinus on the left in the PR and CBCT images were similar to those of the right. While 164 AAA canals (49%) were observed in CBCT images, only 1 (0.3%) was identifiable in PR. Conclusions The results show that CBCT can be recommended for visualising the AAA canal when surgically planning sinus augmentation procedures. Graphical Abstract